2014
DOI: 10.1016/j.cmpb.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk analysis by means of pulse morphology and clustering methodologies

Abstract: c o m p u t e r m e t h o d s a n d p r o g r a m s i n b i o m e d i c i n e 1 1 7 ( 2 0 1 4 ) [257][258][259][260][261][262][263][264][265][266] j o u r n a l h o m e p a g e : w w w . i n t l . e l s e v i e r h e a l t h . c o m / j o u r n a l s / c m p b a b s t r a c tThe purpose of this study was the development of a clustering methodology to deal with arterial pressure waveform (APW) parameters to be used in the cardiovascular risk assessment. One hundred sixteen subjects were monitored and divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Instead, the goal is to learn the relationship between variables and uncover hidden structure in a data set. Examples of unsupervised learning include clustering methods (hierarchical or K means),28 principal component analysis, information maximising component analysis,29 self-organising maps,30 topological data analysis and deep learning. Specifically, deep learning is an emerging subdiscipline of machine learning that leverages an artificial neural network with many hidden layers of neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the goal is to learn the relationship between variables and uncover hidden structure in a data set. Examples of unsupervised learning include clustering methods (hierarchical or K means),28 principal component analysis, information maximising component analysis,29 self-organising maps,30 topological data analysis and deep learning. Specifically, deep learning is an emerging subdiscipline of machine learning that leverages an artificial neural network with many hidden layers of neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Descriptive methods, such as clustering and association rules, disclose concealed patterns that sum up the relationship between variables without predicting target values. Clustering regroups a set of objects with a similar specificity, as used by Almeida et al (2014) in cardiovascular risk assessment where the resulting five clusters showed the intrinsic relation between features. Association rules identify a degree of association between features and their frequency, as achieved by Ou-yang et al (2013) where the impact of prescribed drugs on Stevens-Johnson syndrome was detected.…”
Section: Data Mining and Features Filteringmentioning
confidence: 99%